Consturction and Optimination of Urban Ecological Space Network Based on MSPA Model and Ecological Protection Importance Evaluation - Wang Kun; Ma Chunxu; Zheng Yihan; Tian Xin; Hong Li; Liu Dan (Shuitu baochi tongbao)
[Objective] The construction method for an urban ecological network based on morphological spatial pattern analysis (MSPA) and ecological protection importance evaluation were studied in order to provide a scientific reference for the planning and construction of urban ecological network. [Methods] The importance of ecological protection at Mudanjiang City, Heilongjiang Province was evaluated using the topological superposition of MSPA analysis results, and the birth source area was comprehensively obtained. We used the minimum resistance model to extract potential ecological corridors in the study area, and combined them with gravity models for importance classification. We optimized the ecological network structure from three aspects: source supplement, corridor supplement, and stepping stone supplement. [Results] ① The MSPA analysis results showed that the core area of Mudanjiang City had the highest proportion of landscape types (accounting for 87.41%) and that forest land was the main landscape type. ② There were 10 main ecological sources and six secondary ecological sources at Mudanjiang City. ③ There were 16 potential important ecological corridors and 104 general ecological corridors at Mudanjiang City. ④ Ecological network closure (α index) before optimization was 0.53, and 0.66 after optimization. Number of network connections (γ index) was 0.69 before optimization, and 0.77 after optimization. Line point rate (β index) was 2.0 before optimization, and 2.26 after optimization. [Conclusion] The application of the comprehensive MSPA analysis method and the ecological protection importance evaluation method in ecological network construction can help improve the structure and functionality of the ecological network.